Cost-Effectiveness of an Adjuvanted Hepatitis B Vaccine (HEPLISAV-B) in Patients With Inflammatory Bowel Disease. Issue 1 (7th November 2020) - Corral, Juan E; Kwon, Joshua Y; Caldera, Freddy; Pungpapong, Surakit; Spaulding, Aaron C; Borah, Bijan J; Moriarty, James P; Farraye, Francis A
Abstract: Background: Compare the cost-effectiveness of 2 recombinant hepatitis B virus (HBV) vaccines in patients with inflammatory bowel disease (IBD). Methods: Markov models were developed for 2 IBD cohorts: (1) 40-year-old patients prior to starting IBD treatment and (2) 40-year-old patients already receiving therapy. Cohort A received full vaccination series, cohort B had primary vaccine failure and received a vaccine booster. Two vaccines were compared: adjuvanted HEPLISAV-B and nonadjuvanted Engerix-B. Clinical probabilities of acute hepatitis, chronic hepatitis, cirrhosis, fulminant hepatic failure and death, treatment costs, and effectiveness estimates were obtained from published literature. A lifetime analysis and a US payer perspective were used. Probabilistic sensitivity analyses were performed for different hypothetical scenarios. Results: Analysis of cohort A showed moderate cost-effectiveness of HEPLISAV-B ($88, 114 per quality-adjusted life year). Analysis of cohort B showed increased cost-effectiveness ($35, 563 per quality-adjusted life year). Changing Engerix-B to HEPLISAV-B in a hypothetical group of 100, 000 patients prevented 6 and 30 cases of acute hepatitis; and 4 and 5 cases of chronic hepatitis annually for cohorts A and B, respectively. It also prevented 1 and 2 cases of cirrhosis, and 1 and 2 deaths over 20 years for each cohort. Cost-effectiveness was determined by vaccination costs, patient age, and progression rate from chronic hepatitis to cirrhosis. Conclusions: HEPLISAV-B is cost-effective over Engerix-B in patients receiving immunosuppressive therapy for IBD. Benefits increase with population aging and lower costs of vaccines. We advocate measuring levels of HBV antibodies in patients with IBD and favor adjuvanted vaccines when vaccination is needed. Lay Summary: Treatments for inflammatory bowel disease can reactivate hepatitis B. We used a computer model to evaluate the costs and the protection provided by a new adjuvanted vaccine. The benefits of HEPLISAV-B preventing hepatitis, cirrhosis, and deaths justify the higher costs.